Profil Peredaran Obat Disfungsi Ereksi Ilegal - Fauqi Elfarabi; Fuji Handayani; Yovia Rizki Arrahman; Ari Andriano Santoso (Badan Pengawas Obat dan Makanan, 2021)
Indonesian FDA's data of supervision and law enforcement from 2008 - 2018 show that the trend of finding illegal drugs circulating in Indonesia continued to increase. Erectile dysfunction therapy class drugs dominate the trend of findings, also strengthened by the Indonesian FDA's Public Warning data and the Post Market Alert System report from 2015 - 2017, were widely found traditional medicines containing erectile dysfunction drugs. A study about Profile of Illegal Erectile Dysfunction Drug Circulation is arranged based on data and findings above, in implementing the function of preventing drug and food crime as one of the Indonesian FDA's responsibilities for the availability of efficacious, safe, and qualified medicines. The study aims to identify circulation (including users), the potential value of the circulation of illegal erectile dysfunction drugs in Indonesia, and the potential diversion in the distribution of raw materials for erectile dysfunction drugs using qualitative and quantitative methods. Qualitative methods are carried out through field observations to obtain distribution descriptions, internet surveys, and investigations by undercover, surveillance, and controlled delivery. Quantitative methods are carried out through market surveys using purposive and non-random sampling techniques in 8 (eight) regions in Indonesia, i.e., Jabodetabek, Serang, Padang, Bandung, Semarang, Surabaya, Bali, and Samarinda. The results showed that the distribution of erectile dysfunction drugs offline through permanent kiosks/stalls/carts in Indonesia is still widely found. The online circulation of erectile dysfunction drugs has also increased with the expansion of the market through websites, social media, and e-commerce. The profile of erectile dysfunction drug users is in the productive age group (30-45 years) with income levels between IDR 2,000,000 to IDR 4,000,000, per month and the most consumed brand is Viagra. Potential diversion of the circulation of raw materials for erectile dysfunction drugs occurs in importing raw materials and distributing them from each PBF/importer to the pharmaceutical industry.